The complete mitochondrial genome of the Pink dentex Dentex gibbosus (Perciformes: Sparidae) - Celestina Mascolo; Marina Ceruso; Giuseppe Palma; Aniello Anastasio; Tiziana Pepe; Paolo Sordino (Mitochondrial DNA. Part B. Resources, 2018)
The Pink dentex (Dentex gibbosus, Rafinesque 1810) is one of the most commercially important Sparidae species and it is often subjected to fraud. Here, we report the complete mitochondrial genome of D. gibbosus. The mitogenome is 16,771 bp in length and contained 13 protein-coding genes, 2 rRNA genes, 22 tRNA genes and 2 non-coding regions. The overall base composition of D. gibbosus mtDNA is: 27.8% for A, 28.60% for C, 16.5% for G, 27.05% for T.